Relationship of serum thyroid stimulating hormone with body mass index in healthy adults - Solanki, Amrita (Medknow Publications & Media Pvt Ltd, 2013)
OBJECTIVE: To investigate any possible relationship between serum thyroid stimulating hormone (TSH) with body mass index (BMI) in healthy adults. MATERIALS AND METHODS: A total of 417 subjects aged 18-60 years who volunteered to get screened for thyroid illness with serum TSH have been enrolled from November 2012 to July 2013. Patients were divided into four groups based on BMI value: Underweight (BMI <18 kg/m(2)), normal (BMI: 18-22.9 kg/m(2)), overweight (BMI: 23-24.9 kg/m(2)), and obese (BMI ≥25 kg/m(2)). RESULT: In our study we found a significant variation (P < 0.001) in TSH with increasing BMI. As the BMI increased, mean TSH in the BMI range also increased. The individuals with higher BMI had higher TSH and this trend continued from underweight to Obese. The mean TSH of underweight group was 1.6036 mIU/L, normal weight group 2.1727 mIU/L, overweight group 2.2870 mIU/L and obese group 2.6416 mIU/L. CONCLUSION: In this study we found a significant relationship between serum TSH and BMI and mean TSH increased as BMI increased. Further large scale data from the population is required to confirm our findings.